Identification of Loci Enabling Stable and High-Level Heterologous Gene Expression - Defrel, Gilles; Marsaud, Nathalie; Rifa, Etienne; Martins, Frédéric; Daboussi, Fayza (Frontiers in Bioengineering and Biotechnology, 2021)
Efficient and reliable genome engineering technologies have yet to be developed for diatoms. The delivery of DNA in diatoms results in the random integration of multiple copies, quite often leading to heterogeneous gene activity, as well as host instability. Transgenic diatoms are generally selected on the basis of transgene expression or high enzyme activity, without consideration of the copy number or the integration locus. Here, we propose an integrated pipeline for the diatom, Phaeodactylum tricornutum, that accurately quantifies transgene activity using a -glucuronidase assay and the number of transgene copies integrated into the genome through Digital Droplet PCR (ddPCR). An exhaustive and systematic analysis performed on 93 strains indicated that 42% of them exhibited high -glucuronidase activity. Though most were attributed to high transgene copy numbers, we succeeded in isolating single-copy clones, as well as sequencing the integration loci. In addition to demonstrating the impact of the genomic integration site on gene activity, this study identifies integration sites for stable transgene expression in Phaeodactylum tricornutum.